Factors affecting parents’ satisfaction with online learning during COVID-19: A study on parents of young children - Alaulamie , Lamees Abdulrahman (Journal of Education and e-Learning Research, 2024)
The transition to online learning during the COVID-19 pandemic was a new experience for parents of young children who were obliged to deal with various factors that had an impact on their level of satisfaction. It was essential to address these issues if their children were to continue receiving an education. This research investigates the factors affecting parents’ satisfaction (PS) with their children’s online learning experience during the pandemic. These factors comprised technical support (TS), instructional support (IS), the quality of the online curriculum program (CP) and social interaction (SI). A mixed-methods approach was adopted using a sequential explanatory design. The population sampled for this study comprised parents of young children in Saudi Arabia. The total number of survey respondents was 307 and 12 parents volunteered to be interviewed. The results demonstrated that almost 69% of the variance in parents’ overall satisfaction was predicted by a combination of the aforementioned characteristics. However, SI was found to be the only significant predictor of PS. Overall, the parents’ satisfaction with online learning appeared to be moderate but there were significant differences in PS that related to the parents’ age or the child’s educational level. This study offers insights into online learning experiences and parental satisfaction during the COVID-19 pandemic. Practitioners in the education sector should take this satisfaction into consideration given that parents are an essential element in the success of their children’s online learning experience. Moreover, parents received beneficial information during the pandemic which could help develop the implementation of online learning for future use.